2019
DOI: 10.1002/jlb.2a0118-031rr
|View full text |Cite
|
Sign up to set email alerts
|

Activated NK cells kill hepatic stellate cells via p38/PI3K signaling in a TRAIL-involved degranulation manner

Abstract: NK cells are important in regulating hepatic fibrosis via their cytotoxic killing of hepatic stellate cells (HSCs). NK cells are activated by both cytokines such as IL‐12 and IL‐18, and innate immune stimuli such as ligation of TLRs. The secretion of IL‐18 depends upon activation of the inflammasome, whereas TLRs are stimulated by microbial products. In the case of NK cells, IL‐18 acts synergistically with stimulation of TLR3 to cause cell activation and cytotoxic function. In the present study, we activated N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…It is obvious that liver NK cells via TRAIL and/or NKG2D signaling have a major role in the removal of activated hepatic stellate cells in fibrotic liver or liver cancerous cells as reported in a tetrachloride mouse model of hepatic fibrosis (69, 70). We cannot rule out the contribution liver resident ILC1 in these earlier studies via either cytokine secretion or TRAIL-induced killing of target cells as recently described for activated NK cells (71). Hence, specific host protective roles are assigned to ILC during immune response.…”
Section: Hepatic Nk Cells and Ilc1 In Nafld Developmentmentioning
confidence: 75%
“…It is obvious that liver NK cells via TRAIL and/or NKG2D signaling have a major role in the removal of activated hepatic stellate cells in fibrotic liver or liver cancerous cells as reported in a tetrachloride mouse model of hepatic fibrosis (69, 70). We cannot rule out the contribution liver resident ILC1 in these earlier studies via either cytokine secretion or TRAIL-induced killing of target cells as recently described for activated NK cells (71). Hence, specific host protective roles are assigned to ILC during immune response.…”
Section: Hepatic Nk Cells and Ilc1 In Nafld Developmentmentioning
confidence: 75%
“…In addition, NK cells play a key role in the limitation of liver fibrosis through cytotoxicity of activated HSC[71]. Our recent study found a novel mechanism by which NK cells kill HSCs through TRAIL-involved degranulation manner[72]. In HBV infection, HBV-induced suppressive monocytes induce NK cell differentiation into NK-reg with decreased production of IFN-γ and increased IL-10[11].…”
Section: Does Hbv-induced Immune Suppression Contribute To Liver Fibrmentioning
confidence: 99%
“…However, this hypothesis should be confirmed by testing a larger number of samples. The regulation between TRAIL and TANCR in NK cells should be validated due to TRAIL is also considered as a NK cell cytokine [40,41]. The current study focused on regulation occurring in cis, while lncRNAs can also regulate gene expression in trans or directly interact with proteins [13].…”
Section: Discussionmentioning
confidence: 99%